Sports Cardiology Casebook - Pelliccia, Antonio (Springer London : Imprint: Springer, 2009)
Sudden death in athletes engaged in competitive sports is a highly visible, emotionally charged and important public health issue. Substantial progress has occurred in this new area of cardiovascular medicine driven by the recent focus on the most effective and appropriate strategies for screening for the detection of otherwise unsuspected cardiovascular diseases. Detailed guidelines and consensus recommendations represent the criteria with which clinical decisions regarding management and eligibility/disqualification decisions must be decided. However, applying these guidelines is fraught with difficulty. Sports Cardiology Casebook is an important contribution to the understanding of this important and growing area of medicine, compiling a number of practical experiences from international experts illustrating some of the dilemmas implicit in reaching difficult clinical decisions regarding appropriate management of athletes with underlying cardiovascular disease. This book represents a particularly useful addition to the literature for cardiologists, cardiac electrophysiologists and sports medicine physicians enabling them to understand the issues involved and assisting them in making clinical decisions based on the guidelines.